The Civil Rights Movement and its Relationship To the Current Racial and Political Debate in the US - Donia، KERMADI, Ouail Baha Eddine، SOUALAH MOHAMMED (جامعة الوادي Unversity of Eloued, 2019)
The Civil Rights Movement played a huge role in the making of the modern American civilization. It amassed a great following, and was making tremendous strides towards a more equal society for all. The civil rights movement still affects the current political and racial scenes till these days, and what it has resulted in, is still a part of what constitutes the American society. The present study aims to explore the movement, and how through peaceful means of protesting, it managed to get significant results in a short period of time. Then it links the civil rights movement and the current political and racial climate, how the movement’s immense success was slowly fought through different legislations, resulting in a political climate consisting of negligence towards different racial issues. The study then shows the importance of social media and digital media in starting conversations revolving around political and racial issues. The study reveals that a roadmap to an eventual racial equity can be made and followed, but it requires the most important institute of education: the university.
Keywords: Civil Rights, Racism, Trump, Social Media, University.